A random copolymer approach to develop nonfullerene acceptors for all-polymer solar cells. Issue 11 (9th February 2016) - Li, Xiangzhi; Sun, Po; Wang, Yulong; Shan, Haiquan; Xu, Jiaju; Song, Xin; Xu, Zong-xiang; Chen, Zhi-Kuan
Abstract : We report a donor–acceptor type of random copolymer PNDI-TT-TVT as a replacement for fullerene-based acceptors in organic solar cells (OSCs). Abstract : We report a donor–acceptor type of random copolymer PNDI-TT-TVT as a replacement for fullerene-based acceptors in organic solar cells (OSCs). PNDI-TT-TVT is composed of naphthalene tetracarboxylic diimide (NDI) acceptor units, randomly distributed thieno[3, 2- b ]thiophene (TT) and thienylene-vinylene-thienylene (TVT) donor units. OSCs fabricated from a blend of PTB7-Th and PNDI-TT-TVT exhibit a power conversion efficiency of 4.86%, which is significantly higher than the PCEs of the devices based on alternating copolymers of PNDI-TT and PNDI-TVT. The results indicate that random copolymerization is a promising approach to develop novel polymer acceptors for organic photovoltaics.